Manners and Customs of the Indigenous Peoples in the Education Council: Case Bilingual Intercultural Schools in Maracai bo Zulia State - León, Lisbeth; Valenzuela, Luz; Araujo Ferrer, Felipe Rafael (Frónesis, 2022)
The purpose of the study is to strengthen the customs of indigenous peoples on the Education Board of the Intercultural Bilingual Schools in the Municipality of Maracaibo Edo. Zulia. The theoretical foundations are based on: Constitution of the Bolivarian Republic of Venezuela (1999), Rivas (2013), Resolution 058 (2012), among others. It corresponded to the qualitative paradigm. Under the Hermeneutic Dialectic method. The analysis unit will consist of one (01) member Board of Education of the five Schools Intercultural Bilingual Municipality Maracaibo, Zulia State. Guidelines were used as instruments in-depth interviews. The validity of the information is determined by the process of triangulation. It was evident that indigenous peoples over time have lost their worldview, because they have abandoned their customs, cultures, languages, values, beliefs. We conclude that the Constitution of 1999 first recognized the multiethnic and multicultural character of the country, includes a chapter that focuses on the rights of indigenous peoples and opened spaces for indigenous political participation at the national, state and municipal levels.